Interaction of Monetary and Macro-prudential Policies: The Case of Jordan- Credit Gap as an Example - Obeid, Rami; Awad, Bassam (Asian Journal of Economics and Empirical Research, 2018)
This study aims at investigating the extent of interaction between monetary policy and macro-prudential policy in Jordan during the period (2005-2015) using the Vector Error Correction Model (VECM) to check the presence of short-term and long-term impacts of the monetary policy tools in general on the accumulation of systemic risks in the banking system. Systemic risk was measured using the credit gap. The results showed the existence of a statistically significant negative effect of deposit window rate and required reserve ratio on the accumulation of systemic risks, whereas the rediscount rate had a positive effect.